GONE FISHIN’ EFFECTS IN RETURNS - Ramona DUMITRIU; Razvan STEFANESCU (Risk in Contemporary Economy, 2014)
This paper approaches the presence of the Gone Fishin’ effects on returns from 32 advanced and emerging markets during two periods of time: a relative quiet one and a turbulent one. For the first period we found that calendar anomaly was more pregnant on the advanced markets than on the emerging markets. For the second period, the results of our investigation suggest the disappearance of the Gone Fishin’ effects. This process could be explained by the decline in the so called spirit of holiday during turbulent times or by the passing to new phases of the calendar anomaly’s life cycle.